2015
DOI: 10.1021/am507148n
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Modification on Bacterial Adhesion to Titanium-Based Substrates

Abstract: This study examines bacterial adhesion on titanium-substrates used for bone implants. Adhesion is the most critical phase of bacterial colonization on medical devices. The surface of titanium was modified by hydrothermal treatment (HT) to synthesize nanostructured TiO2-anatase coatings, which were previously proven to improve corrosion resistance, affect the plasma protein adsorption, and enhance osteogenesis. The affinity of the anatase coatings toward bacterial attachment was studied by using a green fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
194
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(221 citation statements)
references
References 34 publications
11
194
3
2
Order By: Relevance
“…Additionally, these results further demonstrate that bacteria, such as S. sanguinis, can attach directly onto Ti surfaces without the existence of a previously formed biological pellicle. This observation is in line with a recent study by Lorenzetti et al, 34 which also Abbreviations: aFM, atomic force microscopy; seM, scanning electron microscopy; Ti, titanium; 3D, three-dimensional. …”
Section: S Sanguinis-ti Adhesive Interactionssupporting
confidence: 92%
“…Additionally, these results further demonstrate that bacteria, such as S. sanguinis, can attach directly onto Ti surfaces without the existence of a previously formed biological pellicle. This observation is in line with a recent study by Lorenzetti et al, 34 which also Abbreviations: aFM, atomic force microscopy; seM, scanning electron microscopy; Ti, titanium; 3D, three-dimensional. …”
Section: S Sanguinis-ti Adhesive Interactionssupporting
confidence: 92%
“…As a result, S. aureus can adhere easily on a surface with spikes, whose spacing dimension is lower than the cellular size, by adapting its outer structure to the surface curvature. In these and other examples [23,[42][43][44], the emerging common concept is that the bacterial dimension defines a critical length-scale for bacterial adhesion-structures smaller than the cellular dimension have a negligible effect on bacterial attachment. This idea explains some conventions that have been introduced in the design of surfaces utilised in the food industry, for example, the rule that hygenic steel surfaces must have an average roughness lower than 0.8 µm dictated by the EHEDG (European Hygienic Equipment Design Group) and, additionally, the requirement of R a to be less than 1.6 µm, dictated by the ISO 4287 standard for cleanability [31,37].…”
Section: Requirements For the Design Of Anti-biofouling Surfacesmentioning
confidence: 99%
“…9 Pogodin et al 10 have modeled the mechanism by which bacteria interact with these nanopillars previously, suggesting that bacteria will rupture upon attempts to adhere to these nanorough surfaces. 11 Additionally, it is known that many biological tissues have nanoscale structures to provide the necessary scaffolds for healthy function, such as the strength and flexibility of bones due to the incorporation of nanocrystal bone minerals (single nm scale) in a matrix of 500 nm collagen fibers. 12 For these reasons, nanofeatures have been incorporated into several engineered biomaterials to prevent bacterial colonization as well as to improve mammalian cell integration and reduce inflammatory responses to these materials.…”
Section: Introductionmentioning
confidence: 99%
“…13 While many treatments can create similar roughness measurements, such as adding coatings onto the surface via electrophoretic deposition, 2 electrochemical anodizing [14][15][16] and silver nanoparticle-embedded hydrogelbased coatings, 17 the morphology of the resulting surfaces can vary drastically. Lorenzetti et al 11 used hydrothermal treatments to generate nanorough surfaces on titanium and found that macro-and microscale grooves (results of the initial material machining process) provided niches for bacteria to adhere and proliferate on, despite high roughness values. Silver is one of the most prominent non-small-molecule drugs used for antibacterial applications, 3,[17][18][19] but can be expensive and mildly toxic to surrounding mammalian cells.…”
Section: Introductionmentioning
confidence: 99%